6.182 Problems 18101 to 18200

Table 6.363: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

18101

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 0 \]

18102

\[ {}2 y^{\prime \prime \prime }+y^{\prime \prime }-5 y^{\prime }+2 y = 0 \]

18103

\[ {}v^{\prime } = g -\frac {k v^{2}}{m} \]

18104

\[ {}x^{2}-2 y^{2}+x y y^{\prime } = 0 \]

18105

\[ {}x^{2} y^{\prime }-3 x y-2 y^{2} = 0 \]

18106

\[ {}x^{2} y^{\prime } = 3 \left (x^{2}+y^{2}\right ) \arctan \left (\frac {y}{x}\right )+x y \]

18107

\[ {}x \sin \left (\frac {y}{x}\right ) y^{\prime } = y \sin \left (\frac {y}{x}\right )+x \]

18108

\[ {}x y^{\prime } = y+2 x \,{\mathrm e}^{-\frac {y}{x}} \]

18109

\[ {}x -y-\left (x +y\right ) y^{\prime } = 0 \]

18110

\[ {}x y^{\prime } = 2 x +3 y \]

18111

\[ {}x y^{\prime } = \sqrt {x^{2}+y^{2}} \]

18112

\[ {}x^{2} y^{\prime } = 2 x y+y^{2} \]

18113

\[ {}x^{3}+y^{3}-y^{2} y^{\prime } x = 0 \]

18114

\[ {}y^{\prime } = \left (x +y\right )^{2} \]

18115

\[ {}y^{\prime } = \sin \left (x -y+1\right )^{2} \]

18116

\[ {}y^{\prime } = \frac {x +y+4}{x -y-6} \]

18117

\[ {}y^{\prime } = \frac {x +y+4}{x +y-6} \]

18118

\[ {}2 x -2 y+\left (y-1\right ) y^{\prime } = 0 \]

18119

\[ {}y^{\prime } = \frac {x +y-1}{x +4 y+2} \]

18120

\[ {}2 x +3 y-1-4 \left (1+x \right ) y^{\prime } = 0 \]

18121

\[ {}y^{\prime } = \frac {1-x y^{2}}{2 x^{2} y} \]

18122

\[ {}y^{\prime } = \frac {2+3 x y^{2}}{4 x^{2} y} \]

18123

\[ {}y^{\prime } = \frac {y-x y^{2}}{x +x^{2} y} \]

18124

\[ {}\left (x +\frac {2}{y}\right ) y^{\prime }+y = 0 \]

18125

\[ {}\sin \left (x \right ) \tan \left (y\right )+1+\cos \left (x \right ) \sec \left (y\right )^{2} y^{\prime } = 0 \]

18126

\[ {}y-x^{3}+\left (x +y^{3}\right ) y^{\prime } = 0 \]

18127

\[ {}y+y \cos \left (x y\right )+\left (x +x \cos \left (x y\right )\right ) y^{\prime } = 0 \]

18128

\[ {}\cos \left (x \right ) \cos \left (y\right )^{2}+2 \sin \left (x \right ) \sin \left (y\right ) \cos \left (y\right ) y^{\prime } = 0 \]

18129

\[ {}\left (\sin \left (x \right ) \sin \left (y\right )-x \,{\mathrm e}^{y}\right ) y^{\prime } = {\mathrm e}^{y}+\cos \left (x \right ) \cos \left (y\right ) \]

18130

\[ {}-\frac {\sin \left (\frac {x}{y}\right )}{y}+\frac {x \sin \left (\frac {x}{y}\right ) y^{\prime }}{y^{2}} = 0 \]

18131

\[ {}1+y+\left (1-x \right ) y^{\prime } = 0 \]

18132

\[ {}2 x y^{3}+y \cos \left (x \right )+\left (3 x^{2} y^{2}+\sin \left (x \right )\right ) y^{\prime } = 0 \]

18133

\[ {}1 = \frac {y}{1-x^{2} y^{2}}+\frac {x y^{\prime }}{1-x^{2} y^{2}} \]

18134

\[ {}2 y^{4} x +\sin \left (y\right )+\left (4 x^{2} y^{3}+x \cos \left (y\right )\right ) y^{\prime } = 0 \]

18135

\[ {}\frac {x y^{\prime }+y}{1-x^{2} y^{2}}+x = 0 \]

18136

\[ {}2 x \left (1+\sqrt {x^{2}-y}\right ) = \sqrt {x^{2}-y}\, y^{\prime } \]

18137

\[ {}x \ln \left (y\right )+x y+\left (y \ln \left (x \right )+x y\right ) y^{\prime } = 0 \]

18138

\[ {}{\mathrm e}^{y^{2}}-\csc \left (y\right ) \csc \left (x \right )^{2}+\left (2 x y \,{\mathrm e}^{y^{2}}-\csc \left (y\right ) \cot \left (y\right ) \cot \left (x \right )\right ) y^{\prime } = 0 \]

18139

\[ {}1+y^{2} \sin \left (2 x \right )-2 y \cos \left (x \right )^{2} y^{\prime } = 0 \]

18140

\[ {}\frac {x}{\left (x^{2}+y^{2}\right )^{{3}/{2}}}+\frac {y y^{\prime }}{\left (x^{2}+y^{2}\right )^{{3}/{2}}} = 0 \]

18141

\[ {}3 x^{2} \left (1+\ln \left (y\right )\right )+\left (\frac {x^{3}}{y}-2 y\right ) y^{\prime } = 0 \]

18142

\[ {}\frac {-x y^{\prime }+y}{\left (x +y\right )^{2}}+y^{\prime } = 1 \]

18143

\[ {}\frac {4 y^{2}-2 x^{2}}{4 x y^{2}-x^{3}}+\frac {\left (8 y^{2}-x^{2}\right ) y^{\prime }}{4 y^{3}-x^{2} y} = 0 \]

18144

\[ {}\left (3 x^{2}-y^{2}\right ) y^{\prime }-2 x y = 0 \]

18145

\[ {}x y-1+\left (x^{2}-x y\right ) y^{\prime } = 0 \]

18146

\[ {}x y^{\prime }+y+3 x^{3} y^{4} y^{\prime } = 0 \]

18147

\[ {}{\mathrm e}^{x}+\left ({\mathrm e}^{x} \cot \left (y\right )+2 y \csc \left (y\right )\right ) y^{\prime } = 0 \]

18148

\[ {}\left (x +2\right ) \sin \left (y\right )+x \cos \left (y\right ) y^{\prime } = 0 \]

18149

\[ {}y+\left (x -2 x^{2} y^{3}\right ) y^{\prime } = 0 \]

18150

\[ {}x +3 y^{2}+2 x y y^{\prime } = 0 \]

18151

\[ {}y+\left (2 x -y \,{\mathrm e}^{y}\right ) y^{\prime } = 0 \]

18152

\[ {}y \ln \left (y\right )-2 x y+\left (x +y\right ) y^{\prime } = 0 \]

18153

\[ {}y^{2}+x y+1+\left (x^{2}+x y+1\right ) y^{\prime } = 0 \]

18154

\[ {}x^{3}+x y^{3}+3 y^{\prime } y^{2} = 0 \]

18155

\[ {}x y^{\prime }-y = \left (1+y^{2}\right ) y^{\prime } \]

18156

\[ {}-x y^{\prime }+y = x y^{3} y^{\prime } \]

18157

\[ {}x y^{\prime } = x^{5}+y^{2} x^{3}+y \]

18158

\[ {}\left (x +y\right ) y^{\prime } = y-x \]

18159

\[ {}x y^{\prime } = y+x^{2}+9 y^{2} \]

18160

\[ {}y^{2}-y+x y^{\prime } = 0 \]

18161

\[ {}x y^{\prime }-y = 2 x^{2}-3 \]

18162

\[ {}x y^{\prime }+y = \sqrt {x y}\, y^{\prime } \]

18163

\[ {}y-x y^{2}+\left (x +x^{2} y^{2}\right ) y^{\prime } = 0 \]

18164

\[ {}x y^{\prime }-y = x^{2} y^{4} \left (x y^{\prime }+y\right ) \]

18165

\[ {}x y^{\prime }+y+x^{2} y^{5} y^{\prime } = 0 \]

18166

\[ {}2 x y^{2}-y+x y^{\prime } = 0 \]

18167

\[ {}y^{\prime }+\frac {y}{x} = \sin \left (x \right ) \]

18168

\[ {}y^{\prime } = \frac {2 y}{x}+\frac {x^{3}}{y}+x \tan \left (\frac {y}{x^{2}}\right ) \]

18169

\[ {}x y^{\prime }-3 y = x^{4} \]

18170

\[ {}y^{\prime }+y = \frac {1}{1+{\mathrm e}^{2 x}} \]

18171

\[ {}\left (x^{2}+1\right ) y^{\prime }+2 x y = \cot \left (x \right ) \]

18172

\[ {}y^{\prime }+y = 2 x \,{\mathrm e}^{-x}+x^{2} \]

18173

\[ {}y^{\prime }+y \cot \left (x \right ) = 2 x \csc \left (x \right ) \]

18174

\[ {}2 y-x^{3} = x y^{\prime } \]

18175

\[ {}y-x +x y \cot \left (x \right )+x y^{\prime } = 0 \]

18176

\[ {}y^{\prime }-2 x y = 6 x \,{\mathrm e}^{x^{2}} \]

18177

\[ {}x \ln \left (x \right ) y^{\prime }+y = 3 x^{3} \]

18178

\[ {}y-2 x y-x^{2}+x^{2} y^{\prime } = 0 \]

18179

\[ {}x y^{\prime }+y = y^{3} x^{4} \]

18180

\[ {}y^{2} y^{\prime } x +y^{3} = x \cos \left (x \right ) \]

18181

\[ {}x y^{\prime }+y = x y^{2} \]

18182

\[ {}\left ({\mathrm e}^{y}-2 x y\right ) y^{\prime } = y^{2} \]

18183

\[ {}-x y^{\prime }+y = y^{\prime } y^{2} {\mathrm e}^{y} \]

18184

\[ {}x y^{\prime }+2 = x^{3} \left (y-1\right ) y^{\prime } \]

18185

\[ {}x y^{\prime } = 2 x^{2} y+y \ln \left (y\right ) \]

18186

\[ {}y^{\prime } \sin \left (2 x \right ) = 2 y+2 \cos \left (x \right ) \]

18187

\[ {}y y^{\prime \prime }+{y^{\prime }}^{2} = 0 \]

18188

\[ {}x y^{\prime \prime } = y^{\prime }+{y^{\prime }}^{3} \]

18189

\[ {}y^{\prime \prime }-k y = 0 \]

18190

\[ {}x^{2} y^{\prime \prime } = 2 x y^{\prime }+{y^{\prime }}^{2} \]

18191

\[ {}2 y y^{\prime \prime } = 1+{y^{\prime }}^{2} \]

18192

\[ {}y y^{\prime \prime }-{y^{\prime }}^{2} = 0 \]

18193

\[ {}x y^{\prime \prime }+y^{\prime } = 4 x \]

18194

\[ {}\left (x^{2}+2 y^{\prime }\right ) y^{\prime \prime }+2 x y^{\prime } = 0 \]

18195

\[ {}y y^{\prime \prime } = y^{\prime } y^{2}+{y^{\prime }}^{2} \]

18196

\[ {}y^{\prime \prime } = y^{\prime } {\mathrm e}^{y} \]

18197

\[ {}y^{\prime \prime } = 1+{y^{\prime }}^{2} \]

18198

\[ {}y^{\prime \prime }+{y^{\prime }}^{2} = 1 \]

18199

\[ {}y y^{\prime \prime } = {y^{\prime }}^{2} \]

18200

\[ {}\left (1-x y\right ) y^{\prime } = y^{2} \]